Magnetic resonance imaging assessed inflammation in the wrist is associated with patient-reported physical impairment, global assessment of disease activity and pain in early rheumatoid arthritis: longitudinal results from two randomised controlled trials. Issue 10 (13th June 2017) - Glinatsi, Daniel; Baker, Joshua F; Hetland, Merete L; Hørslev-Petersen, Kim; Ejbjerg, Bo J; Stengaard-Pedersen, Kristian; Junker, Peter; Ellingsen, Torkell; Lindegaard, Hanne M; Hansen, Ib; Lottenburger, Tine; Møller, Jakob M; et al.
Abstract : Objectives: To examine whether MRI assessed inflammation and damage in the wrist of patients with early rheumatoid arthritis (RA) are associated with patient-reported outcomes (PROs). Methods: Wrist and hand MRIs of 210 patients with early RA from two investigator-initiated, randomised controlled studies (CIMESTRA/OPERA) were assessed according to the Outcome Measures in Rheumatology RA MRI score (RAMRIS) for synovitis, tenosynovitis, osteitis, bone erosions and joint space narrowing (JSN) at baseline, 1 and 5 years follow-up. These features, and changes therein, were assessed for associations with health assessment questionnaires (HAQ), patient global visual analogue scales (VAS-PtGlobal) and VAS-pain using Spearman's correlations, generalised estimating equations and univariate/multivariable linear regression analyses. MRI features were further tested for trends against specific hand-related HAQ items using Jonckheere trend tests. Results: MRI inflammation, but not damage, showed statistically significant associations with HAQ, VAS-PtGlobal and VAS-pain for status and change scores, independently of C reactive protein and swollen joint count. MRI-assessed synovitis was most consistently associated with PROs, particularly VAS-PtGlobal and VAS-pain. MRI-assessed synovitis and tenosynovitis mean scores were positively associated with patient-reported difficulty to cut meat and open a milk carton (p<0.01), and similar patterns were seen for other hand-related HAQ items. Incorporating metacarpophalangeal joints in the analyses did not strengthen the associations between MRI pathology and PROs. Conclusions: MRI-assessed inflammation, but not damage, in early RA wrists is associated with patient-reported physical impairment, global assessment of disease activity and pain and influences the physical function in the hand. Trial registration number: NCT00660647.